Gendered perspectives of the enablers and constraints for female energy leaders in South Africa - Msimanga, Xolile (University of the Witwatersrand, Johannesburg, 2023)
This exploratory research study provides gendered perspectives on female leadership characteristics and how increased diversity may contribute positively to energy sector performance. This study also explored the enablers and constraints for women in the energy sector in South Africa to progress to senior positions. A qualitative research approach was used for the research method. Semi-structured interviews were conducted with eight female and seven male energy sector leaders. Thematic analysis was used to analyse the interview data using MAXQDA coding software. The research findings showed that the characteristics are being people-centric – inclusive and collaborative; 'soft traits' like empathy; developing and empowering others; being visionary and performance-driven. Both genders highlighted that although these characteristics were more pronounced in women, they were also observed in good male leaders. The best leaders can balance their gender-related traits with the traits of good leaders. The leaders highlighted that increased diversity results in better problem-solving and superior solutions. Therefore, an increase in diversity leads to better performingorganisations. The research findings showed that the main enablers were transformation processes; networking and exposure; organisational environment; coaching, mentorship, sponsorship; development and training opportunities; mindset and internal beliefs; senior and managerial support; career ownership; and family support. Self-determination was recognised as vital, and autonomous motivation drove the female leaders to succeed. The research findings showed that the main constraints were gender stereotyping; mindset and internal beliefs; male-dominated sector and culture; old boys’ clubs; lack of female pipelines and representation; lack of accommodative structures in operations; and the dual role of women. Male leaders can play a crucial role in male-dominated environments to ally with women and work on changing the systems. Although gender stereotyping was recognised as the biggest challenge, their mindset and perspectives about the sector were also a significant constraint as it could impact their willingness to pursue leadership roles in energy or even consider careers in the sector.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in Energy Leadership to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Energy sector; enablers; female leadership; constraints; gendered perspectives; self-determination theory; UCTD; SDG-5: Gender equality; SDG-7: Affordable and clean energy